2022
DOI: 10.3390/mi13071088
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in Flexible RF MEMS

Abstract: Microelectromechanical systems (MEMS) that are based on flexible substrates are widely used in flexible, reconfigurable radio frequency (RF) systems, such as RF MEMS switches, phase shifters, reconfigurable antennas, phased array antennas and resonators, etc. When attempting to accommodate flexible deformation with the movable structures of MEMS, flexible RF MEMS are far more difficult to structurally design and fabricate than rigid MEMS devices or other types of flexible electronics. In this review, we survey… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 149 publications
0
3
0
Order By: Relevance
“…Currently, it has not been confirmed that flexible RF MEMS can maintain stable RF performance under conditions of significant bending [59,60]. This is mainly due to the difficulty in reconciling the manufacturing processes of MEMS with high performance [61][62][63]. Flexible RF MEMS switches, with advantages such as conformability, low cost, and impact resistance [52][53][54][55], ensure high-performance, high-integration, and lightweight devices.…”
Section: Capacitive Rf Mems Switchesmentioning
confidence: 99%
“…Currently, it has not been confirmed that flexible RF MEMS can maintain stable RF performance under conditions of significant bending [59,60]. This is mainly due to the difficulty in reconciling the manufacturing processes of MEMS with high performance [61][62][63]. Flexible RF MEMS switches, with advantages such as conformability, low cost, and impact resistance [52][53][54][55], ensure high-performance, high-integration, and lightweight devices.…”
Section: Capacitive Rf Mems Switchesmentioning
confidence: 99%
“…Furthermore, the emergence of new materials, such as piezoelectric polymers and ferroelectric thin films, holds promise for the development of compact and high-performance resonators. These materials exhibit excellent electromechanical properties and can be integrated directly into silicon substrates, enabling the monolithic integration of RF components [16][17][18][19]. Researchers have made significant advancements in the fabrication of Film Bulk Acoustic Resonators (FBARs) using Microelectromechanical Systems (MEMS) technology and compatible Piezoelectric (PZE) materials.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the obvious advantages of using microelectromechanical systems, a fully reliable and long-lifetime solution has not yet been certified for the space environment. On the other hand, a few examples [4][5][6][7][8] used in signal routing have also been studied in the past years [9][10][11] and, more recently, also for the small satellites domain [12][13][14]. For this reason, the RF MEMS solution is still appealing to substitute semiconductor conventional switches or even bulky waveguide switches with planar, miniaturized, and fully passive devices.…”
Section: Introductionmentioning
confidence: 99%